Theory and Applications of Models of Computation 11th Annual Conference, TAMC 2014, Chennai, India, April 11-13, 2014. Proceedings - Gopal, T. V.; Agrawal, Manindra; Li, Angsheng; Cooper, S. Barry; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 11th Annual Conference on Theory and Applications of Models of Computation, TAMC 2014, held in Chennai, India, in April 2014. The 27 revised full papers presented were carefully reviewed and selected from 112 submissions. The papers explore the algorithmic foundations, computational methods, and computing devices to meet today's and tomorrow's challenges of complexity, scalability, and sustainability, with wide-ranging impacts on everything from the design of biological systems to the understanding of economic markets and social networks.
A Roadmap for TAMC -- A tight lower bound instance for k-means++ in constant dimension -- An improved Upper-bound for Rivest et al.$1 (Bs Half-lie Problem -- Reversibility of Elementary Cellular Automata Under Fully Asynchronous Update -- Finite State Incompressible Infinite Sequences -- Finding optimal strategies of almost acyclic Simple Stochastic Games -- The Parameterized Complexity of Domination-type Problems and Application to Linear Codes -- On representations of abstract systems with partial inputs and outputs -- Complexity Information Flow in a Multi-threaded Imperative Language -- An Incremental Algorithm for Computing Prime Implicates in Modal Logic -- Set Cover, Set Packing and Hitting Set for Tree Convex and Tree-like Set Systems -- space complexity of optimization problems in planar graphs -- Fine Tuning Decomposition Theorem for Maximum Weight Bipartite Matching -- Intersection Dimension of Bipartite Graphs -- On the Parameterized Complexity for Token Jumping on Graphs -- More on Universality of Spiking Neural P Systems with Anti-Spikes -- Modular Form Approach to Solving Lattice Problems.s
Keywords: Computer science; Data structures (Computer science).; Computers; Algorithms; Computer logic; Mathematical logic; Computer science -- Mathematics; Computer Science; Theory of Computation; Mathematics of Computing; Algorithm Analysis and Problem Complexity; Logics and Meanings of Programs; Data Structures, Cryptology and Information Theory; Mathematical Logic and Formal Languages; Electronic books